1995
DOI: 10.1063/1.358926
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of PbSe

Abstract: The real (ε1) and imaginary (ε2) parts of the dielectric function, ε(E)=ε1(E)+iε2(E), of PbSe have been measured by spectroscopic ellipsometry in the 1.15–5.4 eV photon-energy range at room temperature. The measured spectroscopic-ellipsometry data reveal distinct structures at three critical-point energies (E1, E2, and E3). These data are analyzed using the two theoretical models, namely, the model dielectric function and standard critical-point model. It is found that both the model dielectric function and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
68
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 19 publications
7
68
1
Order By: Relevance
“…These equations are obtained using the MG effective medium theory and bulk PbSe data at 400 nm ( R ϭ Ϫ10.67, I ϭ 20.54), 35 as optical properties are also bulk-like at this wavelength. In addition to our data, Dai et al 17 recently reported a wavelength-integrated gap, (normalized by a standard peak width of K ϭ 60 nm).…”
Section: Discussionmentioning
confidence: 99%
“…These equations are obtained using the MG effective medium theory and bulk PbSe data at 400 nm ( R ϭ Ϫ10.67, I ϭ 20.54), 35 as optical properties are also bulk-like at this wavelength. In addition to our data, Dai et al 17 recently reported a wavelength-integrated gap, (normalized by a standard peak width of K ϭ 60 nm).…”
Section: Discussionmentioning
confidence: 99%
“…of PbSe nanocrystals deposited on gold by spectroscopic ellipsometry. The dielectric function of the PbSe nanocrystals can be described by a sum of two Lorentz oscillators, as reported before for bulk PbSe [7]. This shape of the dielectric function is determined by an increase of the oscillator strength and the joint density of states near the Van Hove singularities along the directions and in the Brillouin zone [8].…”
mentioning
confidence: 97%
“…Since the width of the oscillator is considerable, the resonance energies are slightly shifted relative to the maximum of im . The spectrum of im obtained at the 8.8 nm nanocrystals resembles that of bulk PbSe [7]. Figure 4 represents the resonance energy of the oscillators as a function of the nanocrystal height.…”
mentioning
confidence: 97%
See 2 more Smart Citations